Comparative Lexico-Morphological Means in Languages (Texas Journal of Multidisciplinary Studies, 2023)
This article is about the means of expressing the relation of comparison, in which the lexicalmorphological means of comparison and the order of their usage in speech are explained in the Uzbek, English and German languages using various examples.